Investigation of finish cut of micro electro discharge milling for nano surface finish - Ali, Mohammad Yeakub; Mehfuz, R. (2008)
In this paper the machining condition to achieve nano surface roughness in finish cut micro electro discharge milling was investigated. The effect of feed rate and capacitance were studied on average surface roughness (Ra), and maximum peak-to-valley roughness height (Ry). Statistical models were developed using three-level twofactor experimental design. Ra and Ry were minimized using desirability function approach. The value of desirability was found to be 98%. The minimum values of Ra and Ry were 23 nm and 173 nm respectively for 1.00 μm s-1 feed rate, 0.01 nF capacitance and 80 volts voltage. Verification experiments were conducted to check the accuracy of the model, where the responses were found very close to the predicted values. The developed models can be used to generate nano surface finish for various microstructures.